Anakinra for Colchicine‐Resistant Familial Mediterranean Fever: A Randomized, Double‐Blind, Placebo‐Controlled Trial. Issue 4 (29th March 2017) - Ben‐Zvi, Ilan; Kukuy, Olga; Giat, Eitan; Pras, Elon; Feld, Olga; Kivity, Shaye; Perski, Oleg; Bornstein, Gil; Grossman, Chagai; Harari, Gil; Lidar, Merav; Livneh, Avi
Abstract : Objective: Familial Mediterranean fever (FMF) is refractory to colchicine prophylaxis in 10–20% of patients. In a number of patient series, treatment with anakinra, an interleukin‐1–blocking agent, prevented FMF attacks in those with colchicine‐resistant FMF. This study was undertaken to evaluate the efficacy and safety of anakinra in the treatment of colchicine‐resistant FMF, using a randomized controlled trial. Methods: Patients with colchicine‐resistant FMF receiving colchicine (dosage ≥1.5 to ≤3 mg/day) were recruited and randomly assigned to receive anakinra or placebo (vehicle). The treatment duration was 4 months. Primary efficacy outcomes were the number of attacks per month, and the number of patients with a mean of <1 attack per month. Quality of life was assessed using a 0–10‐grade visual analog scale (VAS), and safety was assessed according to the number and severity of adverse events. Results: Twenty‐five patients with colchicine‐resistant FMF (14 women) were enrolled, of whom 12 were randomized to receive anakinra and 13 to receive placebo. The mean ± SD number of attacks per patient per month was 1.7 ± 1.7 in those receiving anakinra and 3.5 ± 1.9 in those receiving placebo ( P  = 0.037). Six patients in the anakinra group, compared to none in the placebo group, had <1 attack per month ( P  = 0.005). A beneficial effect of anakinra was noted in the number of attacks in the joints per month in patients receiving anakinra (mean ± SD 0.8 ± 1.6 versus 2.1 ± 1.1 in the placebo group; P  = 0.019) and in quality of life (mean ± SD VAS score 7.7 ± 2.3 in the anakinra group versus 4.2 ± 2.9 in the placebo group; P  = 0.045). The number of adverse events per patient per month was comparable between the anakinra group and the placebo group (mean ± SD 2.03 ± 1.75 versus 3.34 ± 2.5; P  = 0.22). There were no severe adverse events. Conclusion: In this randomized controlled trial, anakinra appears to be an effective and safe treatment for colchicine‐resistant FMF.